Islam dan Masa Depan Hak Asasi Manusia Menurut Abdullah Ahmed Al-Na’im - Musarrofa, Ita (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
The reality of the modern world necessitates a Muslim to rethink about how to be a Muslim in the middle of the interdependence of security, politics, social and culture. This makes Abdullah Ahmed al-Na'im, a Sudanese Muslim intellectual, be restless. The provision of international legal guarantees for the implementation of the collective right of every nation to self-determination make Muslims play the majority of mobilizing their identity in the form of an Islamic state and the implementation of shari’ah itself. However, the affirmation of the collective right to self-determination must be placed within the framework of providing justice for all citizens regardless of sex, race and religion. Herein lies the problem of the implementation of Islamic shari’ah. It is because in some cases, the implementation of Islamic shari’ah actually violates Human Rights, especially the rights of women and non-Muslims. Al-Na'im seeks a peaceful path that Human Rights which established by the United Nations gets the legitimacy of Islam, so that the implementation of the collective right to self-determination by Muslims is not contrary to the values of Human Rights that have been declared universally.